PENGARUH KONSERVATISME AKUNTANSI DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Putri, Nabila Novanda; Effendy, Lukman; Isnaini, Zuhrotul (Jurnal Ilmu Akuntansi, 2022)
The financial performance of the firm is a measure of the success that the company has had in creating profits for the company. The research has the aim of knowing the effect of accounting conservatism and capital structure on the disclosure of the company’s financial performance. Purposive sampling was used for this study with a sample of 121 companies. Documentation technique is used to obtain research data. Data analysis used panel data regression. The results showed that accounting conservatism and capital structure had no partial effect on the company's financial performance.